Geo drug addicts system: one stop information centre system for drug addicts in Malaysia / Aminah Farisha ... [et al.] - Farisha, Aminah (College of Built Environment, 2023)
Drug addiction is a major public health concern in Malaysia, with a significant impact on individuals, and communities.